Chemical Composition Acorus Calamus L. (The Peerian Journal, 2023)
In this article, the information on the chemical composition of the prospective medicinal plant Acorus calamus in Uzbekistan is presented. There are 2 species belonging to the genus Acorus L., and the species Acorus calamus L. is found in Uzbekistan. The plant contains bitter acorin glycoside, 25% starch, tar, alkaloids and flavoring substances, tannins, up to 150% vitamin C and vitamin B. The composition of the essential oil includes pinene, camphene, camphor, merneol, eugelol, azarone, guaene, selinene, acorone, roazilene and other substances.